(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the doctrine of the Divine Attributes in the thought of Khoja Muhammad Parsa (1349–1420), one of the most prominent representatives of the Khwajagan Naqshbandiyya tradition and a leading theoretician of Sufism in Central Asia. Drawing primarily upon his work Tahqiqat, the study analyzes Parsa’s understanding of divine knowledge (marifah), the relationship between theological and experiential cognition of God, and his interpretation of the Ninety Nine Beautiful Names of Allah. Particular attention is devoted to his exposition of the Divine Names al Wakil and al Matin, through which he elucidates the concepts of divine agency, absolute power, human dependence upon God, and spiritual self realization. The article further highlights the significance of Parsa’s scholarly legacy within the intellectual history of Islamic theology and Sufism and demonstrates the importance of his writings as primary sources for the study of the Naqshbandi tradition in Central Asia.